ANALISIS KINERJA ANGGARAN PENDAPATAN DAN BELANJA DAERAH PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KABUPATEN TORAJA UTARA - Tendengan, Jelin; Kannapadang, Dwibin; Mengga, Grace Sriati (ITB AAS Indonesia Surakarta, 2024)
This study aims to determine and analyze the performance of the revenue and expenditure budget at the Regional Financial and Asset Management Agency of North Toraja Regency from 2021-2023. This research uses quantitative methods with data collection techniques carried out through the Realization Report of Revenue and Expenditure at the Regional Financial and Asset Management Agency of North Toraja Regency. The results of this study indicate that the Performance of Regional Revenue and Expenditure of North Toraja Regency in terms of the Independence Ratio is still very low with an Instructive relationship pattern with an average ratio of 5.1%. And the Efficiency Ratio is classified as efficient with an average ratio of 92.5%. Keywords : Budget, Revenue, and Regional Expenditure